Bio-based acrylated epoxidized jatropha oil incorporated with graphene nanoplatelets in the assessment of corrosion resistance coating - Li, Wong Jia; Aung, Min Min; Rayung, Marwah; Ngee, Lim Hong; Fui, Mark Lee Wun (Elsevier, 2023)
Vegetable oil has been extensively investigated as a precursor to the eco-friendly coating as an alternative to petrochemical-based resources due to its lower carbon footprint properties. In view of this, jatropha oil (JO), a type of non-edible oil, has received significant attention in this field. The present study was undertaken to utilize acrylated epoxidized jatropha oil (AEJO) resin and to evaluate the anti-corrosion performance with the addition of graphene nanoplatelets (GNP). AEJO-GNP nanocomposites coatings were obtained after three passes of ultraviolet (UV) irradiation. The corrosion protection of all nanocomposites coatings was investigated by electrochemical measurements. The results showed that the corrosion performance of AEJO-GNP nanocomposites coatings improved from the blank coating. Among all coatings tested, AEJO-0.5 wt% GNP exhibited the strongest barrier property and maximum performance in corrosion protection. The result was supported by water contact angle and pull-off adhesion tests. In addition, the highest pull-off adhesion strength for GNP fillers added coatings was established at 0.5 wt% of GNP. High hydrophobicity and pull-off adhesion strength coatings provided a physical barrier that created a tortuosity pathway for corrosive electrolytes to reach the metal surface and thus showed better anti-corrosion resistance. Thus, nanocomposites coatings with 0.5 wt% GNP exhibited the best anti-corrosive efficacy and surface coating property.